Compressible and Recyclable Monolithic g-C3N4/Melamine Sponge: A Facile Ultrasonic-Coating Approach and Enhanced Visible-Light Photocatalytic Activity - Yang, Ye; Zhang, Qian; Zhang, Ruiyang; Ran, Tao; Wan, Wenchao; Zhou, Ying (Frontiers in Chemistry, 2018)
Powdery photocatalysts seriously restrict their practical application due to the difficult recycle and low photocatalytic activity. In this work, a monolithic g-C3N4/melamine sponge (g-C3N4/MS) was successfully fabricated by a cost-effective ultrasonic-coating route, which is easy to achieve the uniform dispersion and firm loading of g-C3N4 on MS skeleton. The monolithic g-C3N4/MS entirely inherits the porous structure of MS and results in a larger specific surface area (SSA) than its powdery counterpart. Benefit from this monolithic structure, g-C3N4/MS gains more exposed active sites, enhanced visible-light absorption and separation of photogenerated carriers, thus achieving noticeable photocatalytic activity on nitric oxide (NO) removal, rhodamine B (RhB) degradation and CO2 reduction. Specifically, NO removal ratio is as high as 78.6% which is 4.5 times higher than that of the powdery g-C3N4, while RhB degradation rate reaches 97.88%, and yield rate of CO and CH4 attains 7.48 and 3.93 μmol g-1 h-1. Importantly, the features of low-density, high porosity, good elasticity and firmness, not only endow g-C3N4/MS with flexibility in various environmental applications, but also make it easy to recycle and stable for long-time application. Our work provides a feasible approach to fabricate novel monolithic photocatalysts with large-scale production and application.